ANALYSING SEGMENTING, TARGETING, AND POSITIONING TO FORMULATE GLOBAL MARKETING STRATEGY FOR ASAHAN’S OPAK CRACKERS - Fathan Ariq; Nailul Muna; Nurhaliza; Rhama Fahrezy Syumantra; Suhairi (Journal of Social Research, 2022)
This study aims to determine the analysis of Segmenting, Targeting and Positioning to Formulate Asahan's "Opak Opak" Global Marketing Strategy. The research methodology used is qualitative. Qualitative research approach is research that presents and data based on the results of documentation that can provide a clear picture of the object under study, to be processed and analyzed to draw conclusions. The data analysis method used is qualitative where the data used in the study describes an object or phenomenon based on things that generally cannot be calculated using documentation data, literature studies, and secondary data. In this study, the policy analysis of segmenting, targeting and product positioning strategies to formulate a global marketing strategy for Opak Asahan Crackers SMEs is to use effective strategy formulation which finally results in an aggressive SO strategy, namely a strength strategy that takes advantage of the opportunities owned by the business, namely: further improving the management system that is Effective and efficient, Increasing human resources to remain trusted by consumers, Determining market segmentation, target market and product positioning, and Dare to enter the Global market